The immunoglobulin superfamily protein differentiation of embryonic stem cells 1 (dies1) has a regulatory role in preadipocyte to adipocyte conversion. - Gang Ren; Cameron Beech; Cynthia M Smas (PLoS ONE, 2013)
Differentiation of Embryonic Stem Cells 1 (Dies1) was recently identified as a novel type I immunoglobulin (IgG) domain-containing plasma membrane protein important for effective differentiation of a murine pluripotent embryonic stem cell line. In this setting, Dies1 enhances bone morphogenetic protein 4 (BMP4) signaling. Here we show Dies1 transcript expression is induced ∼225-fold during in vitro adipogenesis of 3T3-L1 murine preadipocytes. Immunocytochemical imaging using ectopic expression of Flag-tagged Dies1 in 3T3-L1 adipocytes revealed localization to the adipocyte plasma membrane. Modulation of adipocyte phenotype with with tumor necrosis factor-α (TNFα) treatment or by siRNA knockdown of the master pro-adipogenic transcription factor peroxisome proliferator activated receptor gamma (PPARγ) resulted in a 90% and 60% reduction of Dies1 transcript levels, respectively. Moreover, siRNA-mediated Dies1 knockdown in 3T3-L1 preadipocytes inhibited adipogenic conversion. Such cultures had a 35% decrease in lipid content and a 45%-65% reduction in expression of key adipocyte transcripts, including that for PPARγ. The standard protocol for full in vitro adipogenic conversion of committed preadipocytes, such as 3T3-L1, does not include BMP4 treatment. Thus we posit the positive role of Dies1 in adipogenesis, unlike that for Dies1 in differentiation of embryonic stem cells, does not include its pro-BMP4 effects. In support of this idea, 3T3-L1 adipocytes knocked down for Dies1 did not evidence decreased phospho-Smad1 levels upon BMP4 exposure. qPCR analysis of Dies1 transcript in multiple murine and human tissues reveals high enrichment in white adipose tissue (WAT). Interestingly, we observed a 10-fold induction of Dies1 transcript in WAT of fasted vs. fed mice, suggesting a role for Dies1 in nutritional response of mature fat cells in vivo. Together our data identify Dies1 as a new differentiation-dependent adipocyte plasma membrane protein whose expression is required for effective adipogenesis and that may also play a role in regard to nutritional status in WAT.